Risk?related disclosures by non?finance companies: portuguese practices and disclosure characteristics - Oliveira, J.; Rodrigues, L. L.; Craig, R. (Managerial Auditing Journal, 2011)
The purpose of this paper is to assess the risk?related disclosure (RRD) practices in annual reports for 2005 Portuguese companies in the non?finance sector. The paper conducts a content analysis of a sample of 81 companies (42 listed and 39 unlisted). In considering corporate governance effects, the sample is reduced to the 42 listed companies that are required to disclose a corporate governance report. Implementation of IAS/IFRS and the European Union's Modernisation Directive in 2005 did not affect the quantity and quality of RRD positively. Disclosures are generic, qualitative and backward?looking. Public visibility (as assessed by size and environmental sensitivity) is a crucial influence in explaining RRD: companies appear to manage their reputation through disclosure of risk?related information. Agency costs associated with leverage are important influences also. In listed companies, the presence of independent directors improves the level of RRD. Content analysis does not allow readily for in?depth qualitative inquiry. The coding instrument is subject to coder bias. Information about risk can be provided in sources other than annual reports. The study is confined to one year/one country and pre?dates the global financial crisis (GFC) (2008) and the implementation of IFRS 7 (2007). The results point to the desirability of enhancing accountability by mandating further disclosure of substantive and relevant risk?related information in company annual reports. The RRD observed are shown to be explained by a confluence of agency theory, legitimacy theory and resources?based perspectives.